Creation of a Middle Communicating Artery With External Carotid Artery-Radial Artery Graft-M2 Middle Cerebral Artery Interpositional Bypass and M2 Middle Cerebral Artery-M2 Middle Cerebral Artery Reimplantation for a Recurrent Middle Cerebral Artery Aneurysm: 2-Dimensional Operative Video. Issue 1 (6th August 2020) - Frisoli, Fabio A; Catapano, Joshua S; Benner, Dimitri; Lawton, Michael T
Abstract: Dolichoectatic aneurysms of the middle cerebral artery (MCA) bifurcation pose unique treatment challenges. 1 One treatment consists of an extracranial-intracranial (EC-IC) interpositional bypass and double-reimplantation of the M2 divisions. 2-8 We present a variation of this construct in which an M2 MCA-M2 MCA end-to-side reimplantation was performed, creating a middle communicating artery (MCoA). The patient, a 61-yr-old woman, had previously undergone a "picket fence" clip reconstruction of an unruptured, giant left MCA bifurcation aneurysm in 2014. 9 After the patient provided informed written consent for treatment, a 5-yr surveillance angiogram revealed substantial aneurysm regrowth opposite the clips. A pterional craniotomy was performed, and the aneurysm was exposed through a transsylvian approach. Proximal external carotid artery-radial artery graft (ECA-RAG) anastomosis was performed to arterialize the graft. The distal RAG was anastomosed end-to-side to the temporal division of the M2 segment, and the vessel proximal to the bypass inflow was transected from the aneurysm. We repurposed this "dead-end" as an MCoA by end-to-side reimplantation onto a branch of the frontal M2 trunk. The superior trunk was then clip occluded at its origin at the aneurysm. The aneurysm could not be proximally occluded due to lenticulostriate arteries arising from the back of the bifurcation. Postoperative angiography confirmed patency of the MCoA and its donor bypasses. The aneurysm no longer filled, and the lenticulostriate arteries were preserved. The patient was discharged on postoperative day 3 and made an excellent recovery (3-mo modified Rankin Scale [mRS] = 1). The MCoA is a novel construct that redistributed flow from the interpositional graft into the superior trunk, without the need for additional ischemia time while working with the inferior trunk. Used with permission from Barrow Neurological Institute .